Developing instructional materials of English morphology for English department college-learners - Chothibul Umam (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2015)
The role of knowledge on English Morphology for the students of English Language Education (henceforth ELE) cannot be neglected. However, the preliminary observations done by the researcher during the instructional process of English Morphology at the State College for Islamic Studies (STAIN) Kediri Indonesia, for three academic years shows that most of the students still get difficulty in understanding the course content. The researcher, therefore, is of the opinion that the instructional materials used in the classes need to be developed. The adaptation version of Borg & Gall (1983) model of R & D covering preliminary observation, designing preliminary product, expert validation, product revision, field testing or try out, and revision to produce final product is used to develop an instructional material on English Morphology. The products mostly concern on 1) the course content, 2) the exercises, and 3) the level of language difficulty or word choice. The researcher expects that the final product of this study could be used as a handbook for the students in studying English Morphology.